Modified Hinderer’s Technique for Serious Proximal Hypospadias with Ventral Curvature: Outcomes and Our Experience - Ciftci, Ilhan; Gunduz, Metin; Sekmenli, Tamer (Urology Journal, 2019)
Purpose: Hypospadias is a congenital anomaly that includes defi¬cient ventral structure of the penis. Proximal hypospadias cases make up 20% of all hypospadias cases. The choice of operative technique for hypospadias repair depends on the severity, and it is influenced by the surgeon’s experience and perception of where priorities should lie. Several other factors interact to determine the type of repair, such as meatal site, presence of chordee, availability of the prepuce, and quality of the urethral plate and in addition surgeon’s experience affects the type of repair. Materials and Methods: The treatment records of 42 penoscrotal and perineal hypospadias cases that were treated in our clinic from 1998 to 2017 were reviewed retrospectively. Cases with penoscrotal and perineal meatus were included in the study at the beginning of the urethroplasty. All cases had surgical intervention via Hinderer’s technique. Results: Acceptable cosmetic results were obtained in 37 (85%) patients with an objective scoring system (HOSE) for evaluating the results of hypospadias surgery score. The mean score after surgery was 14.8. Fistula and wound breakdown occurred in 7 out of the 42 cases. Conclusion: In conclusion, the modified Hinderer’s technique is a safe and reliable technique for both proximal and perineal hypospadias. Low complication rates and application in a single surgical session increase the comfort of both the patient and the surgeon.